(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
After Uzbekistan gained independence, the development of the information and communication system led to the emergence of new directions in science. One of these new areas is corpus linguistics. It was about determining the relevance of studying the principles of holistic enjoyment of priceless works created in the native language, creating conditions for preserving the riches of the native language for the future generation and achieving the place of our language in the global global network.